UTILIZATION OF FLYASH WASTE AS REINFORCEMENT OF ALUMINUM MATRIX COMPOSITE PRODUCED USING POWDER METALLURGY (Pemanfaatan Limbah Abu Terbang sebagai Penguat Aluminium Metal Matrix Composite Dibuat dengan Cara Meta/urgi Ser - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Aluminum matrix composite (AMe) has been prepared from aluminum fine powder as a matrix and fly ash waste as reinforcement. In this research the amount of fly ash as much as 2.5,5, 7.5 and 10 wt% was added to the aluminum fine powder. The mixture was compacted using uniaxial with a pressure of 100 MPa and it was pressureless sintered in argon atmosphere at various temperature of 500°, 525°, 550°,575° and 600°C. Bending strength of AMC was determined using four point bending, hardness was tested using Vickers method, wear rate was tested using pin on disk method, porosity was tested using Archimedes method and the micro structure was observed using SEM. The result shows that fly ash can be used as reinforcement of AMC. The bending strength and Vickers hardness of AMC increase, wear rate and porosity of AMC decrease with increasing the fly ash content up to 7.5 wt%, while fly ash higher than 7.5 wt% causes a decrease. Porosity, bending strength, wear rate and hardness of AMC are 5.4%, 68.5 MPa, 0.0571 mg/(MPa.m) and 62.6 VHN, respectively. It shows that bending strength, hardness and wear resistance of AMC are higher than pure aluminum.